Light Manipulation in Metallic Nanowire Networks with Functional Connectivity. Issue 5 (27th December 2016) - Galinski, Henning; Fratalocchi, Andrea; Döbeli, Max; Capasso, Federico
Abstract : Guided by ideas from complex systems, a new class of network metamaterials is introduced for light manipulation, which are based on the functional connectivity among heterogeneous subwavelength components arranged in complex networks. The model system is a nanonetwork formed by dealloying a metallic thin film. The connectivity of the network is deterministically controlled, enabling the formation of tunable absorbing states.